Teaching English Speaking Ability by Using Expression Like and Dislike through Dialogue - Gunawan; Abdul Rahman (Cendekiawan Indonesia Timur, 2022)
The purpose of this study was to determine if the students improved in speaking skills in teaching English by using expressions like and dislike through dialogue in the tenth grade at MAN 1 Watampone. The research uses a descriptive quantitative method with Classroom Action Research (CAR) one group pretest and post-test design. The data analysis involves computing the frequency and percentage of the student's score, mean score, and The Percentages of the students' improvement in speaking ability. The results of the analysis in the study show that teaching speaking using the expression likes and dislikes through dialogue is quite successful. The Dialogues used was effective, especially for speaking skills so, it can be used as an alternative method in teaching speaking based on the results obtained from the post-test results of class X1 students at MAN 1 Watampone for the 2020-2021 academic year.